Instrumen Pengukuran Kelelahan pada Anak Usia Pra Sekolah dengan Leukemia - Gusgus Ghraha Ramdhanie; Bambang Aditya Nugraha (Journal of Telenursing (JOTING), 2023)
This study aims to identify fatigue instruments in preschool children with leukemia. The method used is a narrative review by tracing articles on the CINAHL and Pubmed databases. The results showed that as many as five pieces followed the research focus. The researchers found that the Parent Fatigue Scale (PFS), Child Fatigue Oncology (FO-a), PedsQL, and Childhood Cancer Fatigue Scale were fatigue measurement instruments that could be used in preschoolers with leukemia. In conclusion, the fatigue instrument in preschool children with leukemia can be used by health workers to measure the severity of fatigue to improve the quality of life and child development. Keywords: Preschool Age Children, Leukemia, Fatigue Measurement